Islamic credit card adoption : consumer behavioural intention for Islamic Credit Card (ICC) issued by Islamic Banks in Setiawangsa / Raja Nazmi Raja Abdul Muluk Munawar - Raja Abdul Muluk Munawar, Raja Nazmi (Faculty of Business and Management, 2019)
Malaysia is one of many Islamic countries that has implemented Islamic credit card (ICC) along the year since the establishment of Islamic banking in 1984. The number of ICC cardholder has kept positively increase year by year since its introduction as an Islamic banking product for financing purposes. The purpose of this research study was to know the Islamic banking consumers' behavioural intention to adopt ICC as a Shariah-compliant credit card financing. It was also to determine which independent variables such as consumers' attitude, the subjective norms, financial costs and the level of awareness of the consumers that will be the most significant to the dependent variable which is the consumers' intention to adopt ICC. This study used quantitative research design and primary data as it main data. The sample population were the Islamic bank consumers in the area of Setiawangsa and the data have been collected through self-administered questionnaire and through online questionnaire (Google form) via media social to the respective respondents. All the collected data were analysed through inserting the data in SPSS system to get the final findings based on the descriptive, demographic, reliability of variables, correlation and multiple regression analysis. Based on this research finding, it was found out that there are two significant variables toward consumers' behavioural intention to adopt ICC namely the consumers' attitude and subjective norms. While financial cost and level of awareness were not significant and have low relationship toward the dependent variable.